Flame propagation and explosion characteristics of food-based dust as a function of dust concentration - Siti Zubaidah, Sulaiman; Khairiah, Mohd Mokhtar; Wan Zaiton, Wan Sulaiman; Nur Hikmah, Semawia (American Institute of Chemical Engineers, 2024)
A comprehensive grasp of the mechanisms and characteristics of dust explosions holds significant importance in guiding safe operations and risk mitigation measures. This research examined the impact of dust concentration on the flame propagation and explosion characteristics of rice flour and tea dust. The explosion test was carried out in a 20-L spherical chamber and demonstrated that elevating the dust concentration led to increased explosion pressure and flame velocity. Simultaneously, it decreased both the rise initiation time and the peak time. This observation can be attributed to more particles ignited by heat radiation per unit volume and a greater frequency of effective collisions between reactant molecules. These factors enhance mass and heat transfer in preheating and reaction zones, producing more violent pyrolysis. However, tea dust exhibited a slower flame propagation with weaker turbulent flame intensity due to its higher moisture content and larger particle size than rice flour.